Adsorption of Remazol Black B Using Magnetic-Silicane-Graphene Oxide (MM-SiO2/GO) Composite - Fahmiati; Armid; L.O.A. Usman; D. Ismail; L. A. Kadir (Faculty Mathematics and Natural Sciences, Halu Oleo University, 2025)
Adsorption of Remazol Black B dye using a magnetic material composite of iron sand-silica-graphene oxide (MM/SiO2/GO) has been conducted. This study aimed to determine the characteristics of the iron-silica-graphene oxide magnetic material composite and the effects of pH, concentration, contact time, and temperature variations on the composite's adsorption of Remazol Black B dye. The optimum adsorption of Remazol Black B on MM/SiO2/GO occurs at pH 5. The adsorption process tends to follow the Langmuir adsorption isotherm model, with a Langmuir constant value of -70.95 L.g-1. Adsorption of Remazol Black B on MM/SiO2/GO occurs rapidly within 5-30 minutes and continues to increase in capacity until 240 minutes. The kinetics of Remazol Black B adsorption on MM/SiO2/GO followed the second-order pseudo reaction kinetics model, with a k₂ value of 2.47 g/mg.min-1. Effective adsorption of Remazol Black B on MM/SiO2/GO occurred at 40 °C, proceeding spontaneously with a value of ∆G° = -5.131 kJ/mol.